Погребение золотоордынского времени с остатками костюма девочки-кочевницы на Нижнем Псле - Супруненко, А.Б.; Маевская, С.В. (Степи Европы в эпоху средневековья, 2010)
Осуществление реконструкции костюма по его остаткам, выявленным в погребении 1 кургана 9 вблизи с.Волошино, оказалось довольно актуальной задачей. Ведь в более чем 800 кочевнических погребениях 2-й пол.Х1П - XIV в., известных исследователям, при изучении комплексов получено довольно мало сведений относительно состава, деталей и кроя одежды. Поэтому создание новой, научно обоснованной реконструкции костюма девочки-кочевницы, к тому же произведенной по материалам последних раскопок, расширяет представление об ассортименте и особенностях одежды золотоордынского времени, прежде всего, детской. The paper is a supplemental version of the author’s translation into Russian of the monograph “Unique complex of the Golden Horde time near Voloshine” (2005) originally written in Ukrainian which presented the finds of a complex interdisciplinary research of a unique burial of a child from barrow 9 near Voloshino village in the Lower Psiol area in Poltava province in which the remains of a textile-leather costume, footwear, handbags, separate accompanying objects of inventory, and fragments of a horse-drawn vehicle were preserved. The reconstructed elements of a textile-leather costume of a girl-nomad from the Golden Horde time permit us to get an idea of children’s clothes and footwear of this epoch. This would be the first time for such antiquities from the 14th century steppes. The components of the attire comprise a functionally expedient and aesthetically completed “dress” costume of a child. A new scholarly grounded reconstruction of a costume considerably expands our notions of the clothes of the Golden Horde epoch. An odontologic research of bone remains gives an idea of the health of children and the adult population of the forest-steppe area on the left bank of the Dnieper, as well as some data about medical knowledge and facilities at the time.